Field Research on Surface Temperature Characteristics of Faba Brick using Shade and without Shade - Vira Ansari; Eddy Prianto; Agung Dwiyanto (Eduvest - Journal of Universal Studies, 2022)
In reality, brick is a building material used to make walls or walls. As the basic material is clay or clay which is then molded and burned at a certain temperature so that it turns hard like stone and will not soften again when exposed to water. One of the advantages is that it is strong and durable. However, one of the problems faced today is the supply of bricks as a material for making walls/panels which are mostly taken from productive rice fields. There are 3 (three) results of this study, firstly, the surface temperature profile of the east-oriented brick wall is 1.2% hotter than the temperature on the west side in sunny, cloudy and rainy weather. Second. The wall surface temperature profile in cloudy weather has a surface temperature of 64.4% hotter than the ambient air temperature with the research model using shade. And third, the study of the use of shading on the wall model made of FABA proves that it has a significant effect on the magnitude of the thermal value produced.